The Response of Orangutans to a Total Solar Eclipse Event - Didik Prasetyo; Sri Suci Utami-Atmoko; Deni Kurniawan; Erin Vogel (Universitas Nasional Jakarta, 2021)
A complete solar eclipse is a rare event, and we know very little about how other species, including our closest living relatives the primates, react to these events. We observed orangutans on the island of Borneo, Indonesia during a rare astronomical event of a total solar eclipse. Captive orangutans in Nyarumenteng rehabilitation center, Central Kalimantan were observed to document their reaction to this unexpected environmental event. Based on this study that was conducted in 2016, the dramatical behavior demonstrated in the time of the total solar eclipse, and the general response differed between before and after the event. During the total solar eclipse, flanged males tended to increase their social behavior compared to the unflanged males. These findings indicate that the total solar eclipse resulted in an environmental stressor for these captive orangutans.